Retracted Research: (The extent to which appropriate costs contribute to the rationalization of operational decisions in Al - Furat general company for chemical industries and pesticides (Case Study - SAHI, AHMED MAHDI (Journal of Economic, Administrative and Legal Sciences, 2019)
*This research was retracted on February 2, 2024The aim of this research is to assist the management to take scientifically based operational decisions through conducting differential cost analysis in order to distinguish between the appropriate and inappropriate elements due to their influence on the organization decisions in away to accomplish the desired objectives of the decision. The problem of research lies in auditors' lack of clear understanding of cost accounting in business organizations for appropriate and inappropriate costs because of the absence of criteria that distinguish between them for their importance in the organization's adoption of non-routine decisions. The research has come out with a number of results, the most important among them, is that the company in question did not apply the scientific methods in the scientific decision-making process regarding the acceptance of a special order, without conducting a differential analysis of costs for it enables the manager to take such decisions. The research falls into five parts; the first is " the methodology of the study), while the second includes the (theoretical framework of the concept of cost and its classification). The third section deals with (operational decisions), the fourth is concerned with (practice) and the last section is (the conclusions and recommendations, and then the sources).
Keywords: Appropriate costs; Operational decisions; Al-Furat general company for chemical industries and pesticides